Analisis Pengaruh Jumlah Penduduk, Konsumsi Rumah Tangga, Dan Investasi Terhadap Pendapatan Asli Daerah Di D.I. Yogyakarta Sebelum Dan Setelah Pandemi Covid-19 - Ahmad Jumadi; Jurni Hayati (FEB Universitas Sultan Ageng Tirtayasa, 2022)
D.I. Yogyakarta Province before the pandemic had quite good potential in carrying out regional autonomy functions, one of which was Regional Original Revenue as a source of considerable income in carrying out regional development. During this pandemic, there is a decrease in regional original income. The analytical method used is panel data regression using the comment effect model (CEM) method. The data used are secondary data obtained from the Central Statistics Agency and the Regional Development Planning Agency. The results of this study are: 1). population has a negative and significant effect on local revenue; 2). Household consumption has a positive and significant effect on local revenue; 3). Investment has a negative and insignificant effect on the regional original income variable; 4) The Covid-19 pandemic dummy has a significant effect on regional income.